Implementasi Digital Storytelling sebagai Pendekatan Pedagogis dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Venni Arviani; Ezmar Ezmar (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the effect of implementing digital storytelling in learning as a pedagogical approach on improving elementary school students' language skills. The study employed a quantitative approach with a pre-experimental method through a one-group pretest-posttest design. The subjects were 25 fourth-grade students of SD Negeri 2 Kuala, selected through a convenience sampling technique. Data were collected using a language skills test and assessment rubrics for speaking and writing. Data analysis was performed using descriptive statistics, the Shapiro-Wilk normality test, and a paired samples t-test. The results showed that the average pretest score of 35.92 increased to 68.44 in the posttest, with an average difference of 32.52. The statistical test results showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the scores before and after the treatment. These findings indicate that the implementation of digital storytelling has a positive effect on improving elementary school students' language skills and can therefore be an effective alternative learning approach.